2022
DOI: 10.1111/faf.12666
|View full text |Cite
|
Sign up to set email alerts
|

Computer vision and deep learning for fish classification in underwater habitats: A survey

Abstract: Understanding and modelling how fish respond to climate change, habitat degradation and fishing pressure are critical for environmental protection and are crucial steps towards ensuring sustainable natural fisheries, to support ever-growing human consumption (Zarco-Perello & Enríquez, 2019). Effective monitoring is a vital first step underpinning decision support mechanisms for identifying problems and planning actions to preserve and restore the habitats. However, there is still a gap between the complexity o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 144 publications
(195 reference statements)
0
44
0
Order By: Relevance
“…In future work, we will try to expand the scope of our proposed model by adding more datasets and tasks, such as underwater object tracking and counting, since the selfsupervised learning model can be viewed as a generic tool for underwater video processing, which is critical in underwater fish habitat monitoring [56] and the internet of underwater things [57].…”
Section: Discussionmentioning
confidence: 99%
“…In future work, we will try to expand the scope of our proposed model by adding more datasets and tasks, such as underwater object tracking and counting, since the selfsupervised learning model can be viewed as a generic tool for underwater video processing, which is critical in underwater fish habitat monitoring [56] and the internet of underwater things [57].…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning is a sub-field of machine learning composed of interrelated algorithms and concepts used in training a deep neural network (Saleh et al, 2022). One of the main reasons behind the extereme popularity of deep learning is the unprecedented and unparalleled performance it has achieved across different fields especially image recognition.…”
Section: Deep Learningmentioning
confidence: 99%
“…To learn deep features efficiently, researchers found that a modified version of neural networks, i.e. CNN, works very well in the image processing field (Saleh et al, 2022). In the following sections, we will first introduce the basic concepts of neural networks in general and then describe CNNs and explain how they learn and then process input images.…”
Section: Deep Learningmentioning
confidence: 99%
See 2 more Smart Citations